Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 33 peer-reviewed papers on geoenvironmental engineering and sustainability. Topics include: stabilization and remediation of landfills; waste management practices; case studies; and assessment of innovative sustainable methods and materials. GSP 312 will provide practitioners and researchers the latest information on new developments in sustainable geotechnical engineering.
Keywords: Environmental geotechnology -- Congresses.; Environmental geotechnology -- Case studies.; Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Sustainable engineering -- Case studies.; Sustainable engineering -- Congresses.; elektronické knihy; electronic books